The Effectiveness Of Combined Bentonite And Lime In Osmofilter Paper Package For Improving The Quality Of Peat Water - Saputra, Dian; Hasbi, M; ', Budijono (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The peat water has low pH and it can be improved by adding bentonite and lime. The use of lime, however, produced relatively large amount of sediment. To understand the effectiveness of combined bentonite and lime in osmofilter paper package to increase the pH, a study has been conducted on May- July 2016. Combination of 1,7 g bentonite and 1,7 g lime were wrapped using osmofilter paper and were immersed in 2 L of different pH (2,3,4,5 and 6) peat water. After being kept for 45 minutes, the water quality was checked. Results shown that the package of bentonite and lime was effective to improve the pH. In all treatments, the pH increased, ranged from 7 to 9, but the treated water has relatively high colour and organic matter solid. The treated water was use to rear Cyprinus carpio seedlings. By the 4th day, the survival rate of these fish was 90%. Based on data obtained, it can be concluded that the use of combined bentonite, lime and osmofilter paper is effective to improve the quality of peat water, but is may not effective in reducing the colour and organic matter. Keyword : Peat Water, Osmofilter paper, Bentonit and Lime